Comunicando o risco: um olhar sobre a epidemia de zika - Antunes, Michele Nacif (2018)
Risk communication is defined as a process of planning communication of public institutions to face situations of crises or risks, which almost always become media events. Nowadays, more and more, they can also become social media events. And, therefore, social media must be considered when planning communication in the face of emergencies. The purpose of this thesis is to understand the aspects that involve the relationships between a public health emergency, the media and society, and public institutions responsible for risk management, taking as its central axis the role of social media in contemporary society. To take a look at the zika epidemic, some aspects and elements help us. We start from the issued warnings and the declaration of the public health emergency, from the epidemic of meanings in which zika is surrounded, mainly by the context of uncertainty in which it arose. And before society that experiences uncertainty daily, we make brief considerations about the risk. From risk, we move to risk communication and the emergency in public health and the influences that social media operate on this equation. Four studies were developed. In the first one, metassynthesis was performed, in which topics such as the post-truth and the challenges faced by public institutions in this context were also discussed. In the second, a survey of the main communication actions was carried out, based on the official documents that deal with risk communication and the survey of the high resources spent on advertising during the zika epidemic. We concluded that advertising, among other actions, was considered a priority and occupied a prominent place in communication strategies. In the third one, we discuss the use of Facebook as a risk communication tool of public institutions in the response to the zika epidemic. A survey of the postings of the pages of the Ministry of Health and the Government of the State of Espírito Santo related to the topic was carried out, and soon after that, they were categorized according to the subject addressed. It was observed that during the emergence of the zika epidemic, the strategies used in social media do not differ from practices in other media: an invitation to combat mosquitoes. In the fourth study images that aroused more interest and more number of shares on the part of the Internet users from the device in the social network Instagram were analyzed. In the study, we used ImageCloud, an application developed by the Laboratory of Image and Cyberculture Studies (Labic). In summary, we conclude that the current model adopted by risk communication and public health emergencies points to the need for changes that incorporate new strategies and practices that take into account the diverse spaces, scenarios, contexts and existing social processes. In this way, the following question arises: is it possible another form of risk communication and public health emergencies in Brazil? A kind of communication that is anchored in the integration and articulation of several actors in facing the risk?